Electrochemical behaviour of carbon steel in oil (kerosene) in water emulsion in stagnation conditions - Peña Ballesteros, Darío Yesid; Retamoso, Clemente; Vásquez, Custodio (Rev. Téc. Fac. Ing. Univ. Zulia)
Oil in water emulsions, which contain water as a continuous phase, show good conditions to allow a flow of electric current. Therefore, the corrosion process may be promoted for this kind of system. This study point out results obtained in an interface of kerosene in water emulsion and carbon steel; where the kerosene-water ratio varies from 0 to 70%. The emulsion was in stagnated conditions during the tests. The results were analyzed with the electrochemical impedance technique and the behaviour of the metalemulsion interface represent using equivalent circuits under the different conditions tested. The corrosion type was uniform without any evidence of localized attack due to kerosene contents.